2016
DOI: 10.1016/j.eats.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Footprint Reconstruction With a Direct Viewing of the Posterior Insertion Using a Trans-Septal Portal in the Outside-In Anterior Cruciate Ligament Reconstruction

Abstract: We established a technique for femoral tunnel preparation through direct vision of the femoral footprint with maximum preservation to the native anterior cruciate ligament (ACL) remnant using a posterior trans-septal portal. Anterior arthroscopy is difficult for the proper tunnel placement without sacrificing the ACL remnant. Posterior arthroscopy could be helpful for viewing the posterior insertion of the ACL remnant that provides excellent femoral footprint exposure without sacrificing the native ACL remnant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…2A, B). 15,16 The arthroscope was introduced via the PM portal and showed transseptal portal, thereby the opened compartments and anatomical structures could be evaluated (►Fig. 2C, D).…”
Section: Transseptal Portal In Acl Femoral Tunnelingmentioning
confidence: 99%
See 1 more Smart Citation
“…2A, B). 15,16 The arthroscope was introduced via the PM portal and showed transseptal portal, thereby the opened compartments and anatomical structures could be evaluated (►Fig. 2C, D).…”
Section: Transseptal Portal In Acl Femoral Tunnelingmentioning
confidence: 99%
“…[9][10][11][12] Therefore, techniques are being used to attain both aims such as posterolateral (PL) viewing with a 70-degree scope and transseptal portal viewing. [13][14][15][16] However, a 70-degree scope could show some distorted view due to its oblique view displacement. 13 In posterior cruciate ligament (PCL) reconstruction, the femoral footprint of the PCL could be seen easily without sacrificing the remnant PCL.…”
mentioning
confidence: 99%
“…Although ACL anatomy has been described by use of radiographic and cadaveric measures, it is important to understand the anatomy to easy visualize the arthroscopic landmarks. 7 , 8 , 9 , 16 , 24 , 25 Anatomic placement of the femoral and tibial tunnels is crucial to the success of ACL reconstruction. 1 , 2 , 3 , 4 , 19 Although during ACL reconstruction the anatomic positioning is objectified, the maintenance of the bone integrity of the tunnels created is not always guaranteed.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] An alternative approach is to locate the femoral tunnel according to the ligament remnant; however, it can be difficult to accurately identify the ACL footprint with an anterior arthroscope when the remnant is preserved. 16 It has been reported that the femoral tunnel can be located accurately with the quadrant method, and this can be achieved intraoperatively by using fluoroscopy. [17][18][19] However, repeated fluoroscopy is needed during surgery, and the bone can be damaged during readjustment of the position, affecting the location of the guide needle.…”
mentioning
confidence: 99%